2019
DOI: 10.1186/s12896-019-0538-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient preparation of active S-phenyl-L-cysteine with tryptophan synthase using a chemoenzymatic method

Abstract: Background S-Phenyl-L-cysteine is regarded as having potential applicability as an antiretroviral/protease inhibitor for human immunodeficiency virus (HIV). In the present study, optically active S -phenyl-L-cysteine was prepared in a highly efficient manner from inexpensive bromobenzene using tryptophan synthase through a chemoenzymatic method. Results The chemoenzymatic method used a four-step reaction sequence. The process started with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Trans-4-Hydroxy-L-proline Chiral synthon for the chemical synthesis for pharmaceuticals such as antiphlogistics, carbapenems and ACE-inhibitors Taste-enhancing properties and probable health benefits, approved as GRAS ingredient by the FDA. Mu et al, 2015Mu et al, , 2019Yang et al, 2020 18 F-and 11 C -labeled NcAAs Preclinical and clinical tumor PET/CT imaging Sun et al, 2018 α-Vinylic AAs L-Vinylglycine, useful for the study of PLP-dependent enzymes Berkowitz et al, 2006 L-Cys derivatives L-ethionine, S-phenyl-L-cysteine, potential applicability as an antiretroviral/protease inhibitor for HIV Xu et al, 2019;Yu et al, 2019 L-pHFG and derivatives Found in several peptidic natural products including the vancomycin group of antibiotics (e.g., vancomycin, chloroeremomycin, and complestatin) as well as other antimicrobial compounds such as ramoplanin Al Toma et al, 2015 Fluorinated amino acids Different applications in medicinal chemistry (e.g., amino acid decarboxylase inhibitors, bioisosteres, building block for different drugs, . .…”
Section: Patel 2001mentioning
confidence: 99%
“…Trans-4-Hydroxy-L-proline Chiral synthon for the chemical synthesis for pharmaceuticals such as antiphlogistics, carbapenems and ACE-inhibitors Taste-enhancing properties and probable health benefits, approved as GRAS ingredient by the FDA. Mu et al, 2015Mu et al, , 2019Yang et al, 2020 18 F-and 11 C -labeled NcAAs Preclinical and clinical tumor PET/CT imaging Sun et al, 2018 α-Vinylic AAs L-Vinylglycine, useful for the study of PLP-dependent enzymes Berkowitz et al, 2006 L-Cys derivatives L-ethionine, S-phenyl-L-cysteine, potential applicability as an antiretroviral/protease inhibitor for HIV Xu et al, 2019;Yu et al, 2019 L-pHFG and derivatives Found in several peptidic natural products including the vancomycin group of antibiotics (e.g., vancomycin, chloroeremomycin, and complestatin) as well as other antimicrobial compounds such as ramoplanin Al Toma et al, 2015 Fluorinated amino acids Different applications in medicinal chemistry (e.g., amino acid decarboxylase inhibitors, bioisosteres, building block for different drugs, . .…”
Section: Patel 2001mentioning
confidence: 99%
“…Directed evolution can promote the enzymatic activity of lipase, xylanase, a-galactosidases, monoamine oxidase and nitrilase [14][15][16][17][18][19]. L-tryptophan and S-phenyl-L-cysteine were synthesized by tryptophan synthase of Escherichia coli k-12, and it was found that tryptophan synthase has the potential to synthesize L-tryptophan and its derivatives [20][21][22]. In this study, directed evolution of tryptophan synthase was performed by error-prone PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Directed evolution can promote the enzymatic activity of lipase, xylanase, a-galactosidases, monoamine oxidase and nitrilase [14][15][16][17][18][19]. L-tryptophan and S-phenyl-L-cysteine were synthesized by tryptophan synthase of Escherichia coli k-12, and it was found that tryptophan synthase has the potential to synthesize L-tryptophan and its derivatives [20][21][22]. In this study, directed evolution of tryptophan synthase was performed by error-prone PCR.…”
Section: Introductionmentioning
confidence: 99%